Seronegative virus carriers in the infection of rabbits with human T lymphotropic virus type I (The Rockefeller University Press, 1988)
Six HTLV-I-transformed T cell lines were prepared from PBL of three rabbits each of B/J and Chbb:HM strains, and were inoculated into newborn rabbits of these two strains, and of their F1 hybrid. None of three B/J cell lines induced anti-HTLV-I antibody response in newborn B/J rabbits, whereas all three Chbb:HM cell lines did induce a response in newborn Chbb:HM rabbits. These B/J cell lines however could induce antibody response in adult B/J as well as newborn Chbb:HM rabbits, and a Chbb:HM cell line could induce a response in a newborn B/J rabbit. Similar unresponsiveness was observed in (B/J x Chbb:HM)F1 hybrids neonatally inoculated with B/J cells. Unresponsiveness was abrogated by reinoculation of some but not other cell lines. Viral antigen-positive cell lines harboring HTLV-I provirus genomes were established from such seronegative B/J and F1 rabbits. Simultaneous inoculation of HTLV-I- transformed cells and SPV resulted in the induction of papilloma and antibody against SPV, but not antibody against HTLV-I. The present findings thus reveal that neonatal infection of HTLV-I could result in immunological tolerance to the virus antigens, thereby leading to a persistent infection without antibody induction.